THE BASIC STAGES OF REALIZATION OF THE INNOVATION PROJECTS - K.A. BARMUTA (Advanced Engineering Research)
The various approaches to definition of structure of works on performance of the innovation projects are considered, the author's circuit reflecting the basic stages of realization of the projects is offered.